2017
DOI: 10.1007/s00436-017-5712-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus reduces parasite load on Toxocara canis experimental infection in mice, but has no effect on the parasite in vitro

Abstract: Human toxocariasis is a neglected global parasitic zoonosis. The efficacy of drug treatment for this disease has been hindered by the biological complexity of the main etiological agent, the nematode Toxocara canis. Experimental studies have shown the potential of probiotics to promote a reduction in the parasite load of T. canis larvae. This study aimed to evaluate the effect of probiotic Lactobacillus rhamnosus ATCC 7469 on the parasite load of BALB/c mice with acute toxocariasis and evaluate the direct effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
3
8
0
2
Order By: Relevance
“…Next, the colony-forming units (CFU) were determined. Probiotic production, quality control, culture viability, colony counts and purity were evaluated according to the methodology employed by Walcher et al 20 .…”
Section: Probiotic Lactobacillus Acidophilusmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the colony-forming units (CFU) were determined. Probiotic production, quality control, culture viability, colony counts and purity were evaluated according to the methodology employed by Walcher et al 20 .…”
Section: Probiotic Lactobacillus Acidophilusmentioning
confidence: 99%
“…After 48 h of T. canis egg inoculation, mice without supplementation had consistent IFN-γ (G2) gene transcription levels. treat parasitosis, such as Trichinella spiralis, Giardia lamblia and Toxocara canis 20,[33][34][35] . The results obtained in this study have shown that supplementation with L. acidophilus ATCC 4356 has significantly reduced the infection intensity of Toxocara canis larvae in experimentally infected mice.…”
Section: Ifn-γ Gene Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…canis larvae to offspring was observed in G1 group relative to G2 group, and 50% reduction in the number of larvae in the brains of the offspring was observed in G1 relative to G2 ( P = 0.023). These results corroborate previous studies demonstrating promising results of probiotics Enterococcus faecalis CECT7121 (Basualdo et al ., 2007; Chiodo et al ., 2010), Lactobacillus rhamnosus (Walcher et al ., 2018) and S. boulardii (Avila et al ., 2012, 2016; Cardoso et al ., 2020) in altering T . canis larvae infection intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Probiyotik özelliklerin değerlendirilme işlemleri tamamlandıktan sonra, ilgili suşlar in vivo testlere tabi tutulmaktadır (De Melo Pereira et al, 2018). Probiyotiklerle ilgili olarak fare, sıçan ve domuzlarda in vivo testlerin yapıldığı çeşitli çalışmalar mevcuttur (Sarkar et al, 2016;Kim et al, 2018;Walcher et al, 2018). Ancak, çoğu kez artan maliyet ve etik nedenlerden dolayı in vivo testler yapılamamaktadır.…”
Section: Bağırsak Yüzeyine Tutunmaunclassified